Implementing initiatives of women’s empowerment in Higher Education of Uzbekistan: challenges and successes - Munojat Sultonova (Periodica Journal, 2022)
Nowadays, Uzbekistan has been working on several reforms and initiatives to support women’s participation in leading the changes in the society. There is still some discrimination against women in education, health, entrepreneurship and participating in the process of politics in the country. Numerous stereotypical issues are used to describe women’s discrimination, the most common of which are discrimination in education particularly in higher education. Although the image of women in the society is regarded as a mother, a housewife and inactive bystander for participating in changes, the past decades has seen the rapid development of women’s progress in Uzbekistan. However, there are still some barriers which women are facing should be reduced to enhance women’s role in the society for economic growth of the world. This paper will discuss the implementation of women’s development in the society in terms of gender equality in education
Keywords: discuss; bystander; economic; education